Prospective randomized controlled trial on the safety and neuroprotective efficacy of remote administration of hypothermia over spleen during acute ischemic stroke with mechanical thrombectomy: rationale, design, and protocol - Duan, Honglian; Cheng, Zhe; Geng, Xiaokun; Rajah, Gary B.; Gao, Jie; Guo, Yang; Cai, Lipeng; Tong, Yanna; Li, Fengwu; Jiang, Qian; Han, Zhenzhen; Ding, Yuchuan (Frontiers in Neurology, 2024)
Background Brain inflammation plays a key role in ischemia/reperfusion (I/R) injury and is the main cause of “ineffective or futile recanalization” after successful mechanical thrombectomy (MT) in acute ischemic stroke (AIS). One of the primary sources of inflammatory cells after AIS are derived from the spleen. As an innovative and potential neuroprotective strategy after stroke, Remote Administration of Hypothermia (RAH) temporarily suppresses immune activities in the spleen, reduces the release of inflammatory cells and cytokines into blood, and thus reversibly diminishes inflammatory injury in the brain. Methods This single-center, prospective, randomized controlled study (RCT) is proposed for AIS patients with anterior circulation large vessel occlusion (LVO). Subjects will be randomly assigned to either the control or intervention groups in a 1:1 ratio (n = 40). Participants allocated to the intervention group will receive RAH on the abdomen above the spleen prior to recanalization until 6 h after thrombectomy. All enrolled patients will receive standard stroke Guideline care. The main adverse events associated with RAH are focal cold intolerance and abdominal pain. The primary outcome will assess safety as it pertains to RAH application. The secondary outcomes include the efficacy of RAH on spleen, determined by spleen volumes, blood inflammatory factor (cells and cytokines), and on brain injury, determined by infarction volumes and poststroke functional outcomes. Discussion This study aims to examine the safety and preliminary effectiveness of RAH over the spleen during endovascular therapy in AIS patients. The results of this study are expected to facilitate larger randomized clinical trials and hopefully prove RAH administration confers adjuvant neuroprotective properties in AIS treated with MT. Clinical trial registration https://www.chictr.org.cn/. Identifier ChiCTR 2300077052.